Determinants of initial public offerings: The case of Poland - Tomá Meluzín; Marek Zinecker; Justyna Lapinska (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2014)
The main objective of this study is to indicate the in uence of local macroeconomic factors, consequently GDP growth rates, the reference interest rate, industrial production growth rates, Warsaw Stock Exchange Index (WIG) returns and the volume of private equity investments, on the number of initial public offerings (IPOs) in an emerging market, Poland, over the period of 2004 to 2012. Our sample includes 218 local enterprises that conducted an IPO on the Main Market of the Warsaw Stock Exchange. Financial and privatized companies are excluded from the data processing. As follows from the previous studies, the situation in the year preceding the companys initial public offering is crucial. Therefore, we used a model with one-year delay for all the explanatory variables in relation to the dependent variable (i.e. number of new listing). The model estimation was performed with the Ordinary Least Squares method. The main conclusion of our model is that the GDP growth has a significant impact on the number of new issues. This result implies that the business cycle has a direct impact on the IPO activity in the Polish capital market. The next conclusion is that the attractiveness of a capital market for investors measured by annual index returns appears to be an important factor for going public activities. Surprisingly, the model could confirm that other macroeconomic and capital market factors have had no explanatory power for IPO numbers in Poland between 2004 and 2012.
Keywords: E17; G32; 330; Corporate Finance; going public; Initial Public Offering (IPO); determinants; Poland